A Primer on Trauma-Informed Practice in Refugee Law - Glen Cranwell (Bond Law Review)
This article is intended as a primer on trauma-informed practice for professionals working in the area of refugee law. Refugees and asylum seekers are amongst the most vulnerable groups in the community, and the process of seeking asylum itself can intensify stress. Trauma-informed practice is founded on ‘safety first’ and ‘do no harm’. It reflects adherence to core principles, rather than a prescribed set of practices and procedures. The core principles of trauma-informed practice include safety, trust, choice, collaboration and empowerment. This article primarily focusses on professional applications of trauma-informed practice at an individual level. By taking steps to integrate these principles into interpersonal interactions with refugees and asylum seekers, professionals can better support their needs in the refugee law context.